2014
DOI: 10.1186/1472-6882-14-20
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic action of rhodiola-aqeous extract in type1-like diabetic rats

Abstract: BackgroundRhodiola rosea (Rhodiola) is a plant in the Crassulaceae family that grows in cold regions of the world. It is mainly used in clinics as an adaptogen. Recently, it has been mentioned that Rhodiola increases plasma β-endorphin to lower blood pressure. Thus, the present study aims to investigate the antidiabetic action of Rhodiola in relation to opioids in streptozotocin-induced diabetic rats (STZ-diabetic rats).MethodsIn the present study, the plasma glucose was analyzed with glucose oxidase method, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 55 publications
1
11
1
1
Order By: Relevance
“…In STZ‐diabetic rats with heart failure, a 95% ethanol extract of R. rosea (Extract 23 ) showed its ability to increase cardiac output, which was associated with an increase of peroxisome proliferator‐activated receptor‐δ . Meanwhile, a water extract of R. rosea (Extract 24 ) showed antihyperglycemia activity in STZ‐type I diabetic rats via an increase of β‐endorphin secretion in the adrenal gland . In animal models of the metabolic syndrome and type II diabetes, treatment with the powder of a R. crenulata methanol extract (Extract 20 ) resulted in the ameliorated derangements of glucose and lipid metabolism .…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In STZ‐diabetic rats with heart failure, a 95% ethanol extract of R. rosea (Extract 23 ) showed its ability to increase cardiac output, which was associated with an increase of peroxisome proliferator‐activated receptor‐δ . Meanwhile, a water extract of R. rosea (Extract 24 ) showed antihyperglycemia activity in STZ‐type I diabetic rats via an increase of β‐endorphin secretion in the adrenal gland . In animal models of the metabolic syndrome and type II diabetes, treatment with the powder of a R. crenulata methanol extract (Extract 20 ) resulted in the ameliorated derangements of glucose and lipid metabolism .…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…24 Meanwhile, a water extract of R. rosea (Extract 24) showed antihyperglycemia activity in STZ-type I diabetic rats via an increase of β-endorphin secretion in the adrenal gland. 152 In animal models of the metabolic syndrome and type II diabetes, treatment with the powder of a R. crenulata methanol extract (Extract 20) resulted in the ameliorated derangements of glucose and lipid metabolism. 25 In a type II diabetic model of C57BL/Ks db/db mice, an 85% ethanol extract of R. rosea (Extract 22) exhibited antihyperglycemia and diabetic complication effects.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Although several drugs are available for the treatment of T2D, their effect on correcting the dyslipidemia associated with the disease is not obvious. Therefore, drugs which could target both the hepatic gluconeogenesis as well as the lipid metabolism disorder of T2D would serve as promising therapies [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that an ethanol extract of Rhodiola rosea protected diabetic rats from early nephropathy, which may have been associated with the reduced the expression of transforming growth factor β1 (TGF-β1) in renal tissues [71]. A water extract of Rhodiola rosea administered orally to STZ-diabetic rats lowered plasma glucose and improved hyperglycemia, acting via an increase in β-endorphin secretion from the adrenal gland, which activated the opioid μ-receptors [72].…”
Section: Chemical Constituents Of Rhodiolamentioning
confidence: 99%